2021
DOI: 10.2174/1389202922666210601095700
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Analysis of CCGAC and CATGTG Cis-regulatory Elements Across Genomes Reveals their Roles in Gene Regulation under Stress

Abstract: Background: Plant yield closely depends on its environment and is negatively affected by abiotic stress conditions like drought, salinity, heat, and cold. Analysis of the stress-inducible genes in Arabidopsis has previously shown that CCGAC and CATGTG play a crucial role in controlling the gene expression through the binding of DREB/CBF and NAC TFs under various stress conditions, mainly drought and salinity. Methods: The pattern of these motifs is conserved, which has been analyzed in this study to find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…In addition, the GhCKX genes consisted of several cis -elements in their promoter region associated with circadian control, light response, auxin response, abscisic acid response, phytochrome regulatory elements, zein metabolism, low temperature, anaerobic induction, meristem and endosperm expression, elements responding to gibberellin, MeJA, and salicylic acid. Earlier studies identified the light-induced cis-elements GT1 motif, G-box, I-box and AT-rich regions ( Sun et al, 2023 ), AuxRE, DR5, the cis-elements induced by auxin ( Li et al, 2022 ), and the cis-elements CATGTG and CACG induced by cold ( Bhadouriya et al, 2021 ). The abundance of elements in the promoter region of GhCKX genes suggests the functional diversity of these genes in cotton.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the GhCKX genes consisted of several cis -elements in their promoter region associated with circadian control, light response, auxin response, abscisic acid response, phytochrome regulatory elements, zein metabolism, low temperature, anaerobic induction, meristem and endosperm expression, elements responding to gibberellin, MeJA, and salicylic acid. Earlier studies identified the light-induced cis-elements GT1 motif, G-box, I-box and AT-rich regions ( Sun et al, 2023 ), AuxRE, DR5, the cis-elements induced by auxin ( Li et al, 2022 ), and the cis-elements CATGTG and CACG induced by cold ( Bhadouriya et al, 2021 ). The abundance of elements in the promoter region of GhCKX genes suggests the functional diversity of these genes in cotton.…”
Section: Discussionmentioning
confidence: 99%
“…WRKY TFs are involved in drought, salt, and heat response 36 . CCGAC and CAT GTG functions in drought and salinity stress 37 . GT1 and TGA motifs function in response to salt-induced stress 38,39 .…”
Section: Promoter Ps Camv 35smentioning
confidence: 99%